S, Habiby The DSGE model and the optimal monetary rule - Habiby, salwa (Archives of Business Research, 2022)
Inflation targeting policy is a monetary policy framework that ensures a low inflation rate, close to an objective that is usually 2%. Due to deterioration of the relationship between monetary variables and aggregates in many economies, this policy is emerging as a new monetary strategy. Bank Al-Maghrib is part of this process, and thus Morocco has taken the first step in this direction by adopting a more flexible exchange rate regime. Nevertheless, the transition to this regime requires knowledge of the transmission of the interest rate on inflation and output. In this article, we determine the optimal monetary rule to accomplish Morocco’s transition to inflation targeting. We evaluate this rule by first constructing a DSGE model for a closed economy and then estimating through Bayesian estimation four sub-models (four monetary rules). The comparison between models shows that the rule associated with inflation and output targeting with interest rate smoothing allows for better transmission of monetary policy. It is therefore the optimal monetary rule for the eventual implementation of inflation targeting policy in Morocco. Keywords: inflation targeting, credibility, economic growth, Neo Keynesian model, monetary rule.